HUBUNGAN KEBISINGAN DAN SHIFT KERJA TERHADAP TINGKAT STRES KERJA PADA PEKERJA MESIN PEMBANGKIT SWD (STORK WERKSPOOR DIESEL) PLTD GUNUNG MALANG BALIKPAPAN - Fabrianing Nur Rahmawati; Ekawati Ekawati; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Stress is a form of worker response when it comes to the capacity and ability to deal with their work. Stress occurs in a variety of work situations, but stress often occurs when workers feel they have little ability and control to cope with the demands and pressures in the job. One of that affects stress work are work environment that is noise and also work shift. The purpose of this study was to describe and analyze the relationship of age, periode of work, noise and shift work toward work stress on the Stork Werkspoor Diesel worker PLTD Gunung Malang Balikpapan. This study used quantitative method with cross sectional approach. Sample in this research used total population that are all the machine worker of power plant at Gunung Malang Balikpapan. The result of this research showed that majority of respondents were in the category, age more than 40 years (55.3%), period of work more than 10 years (63.2%), noise exposured more than 85 dB(A) (57.9%), and mostly workers are in daily shift work (52.6%). Based on statistical test with Chi Square, showed that there were no correlation between age (p=0,188), period of work (p=0,339), and noise (p=0,206) with stress work. Furthermore, there were correlation between work shift (p=0,003) with stress work. The conclusion in this study was that the work shift are related to work stress on worker.